World diabetes day 2017 focus: antepartum hyperglycaemia (or gestational prediabetes) is more in women below 40 years - M. I., Orru; E. U., Nwose; P. T., Bwititi; E. O., Igumbor (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Prediabetes is a state of hyperglycaemia that is above normal, but below blood glucose threshold for diabetes mellitus. As part of the theme for World Diabetes Day of 2017, it has been articulated by the International Diabetes Federation, that up to 16% of births may be affected by this condition and it is estimated that 50% of the affected antenatal patients are under 30 years old. The notion of gestational prediabetes, hyperglycaemia in pregnancy as a clinical condition is yet to be seriously discussed in regards to prediabetes in pregnancy. Instead, it seems to be subsumed in the discourse of gestational diabetes mellitus. This subsuming position is evident in the fact that even in discussion of management challenges of the ‘hyperglycaemia in pregnancy’ condition, blood glucose thresholds for gestational diabetes refers to higher versus lower cut-offs, but never refers to prediabetes.